Implementation and Analysis of Profiling Mechanism for Anonymity and Privacy on Whonix Operating System - Batunanggar, Yana J S; Widjajarto, Adityas; Kurniawan, M Tegoeh (Journal of Information System Research (JOSH), 2024)
This research will implement anonymity using the Whonix operating system. This research seeks to analyze the features of the Whonix operating system that can support anonymity and privacy profiling, the function of anonymity and privacy profiling on the operating system, and the character of the operating system capable of maintaining anonymity and privacy. Features owned by the Whonix operating system that support anonymity and privacy profiling on Whonix are application, network, and operating system aspects, as well as analyzing anonymity and privacy functions with metrics. This research produces metrics on each aspect. The application aspect obtained metrics of data encryption, metadata protection, and privacy by design by analyzing profiling experiments on KeePassXC and GnuPG applications. The network aspect uses Tor compatibility, IP Address obfuscation, and logging policy metrics by analyzing profiling experiments on Wireguard and DNSLeakTest. While the operating system aspect uses data encryption, logging and monitoring, and access control metrics by analyzing profiling experiments with fingerprinting and backup and restore scenarios. The results of this study obtained scoring profiling of the Whonix operating system, application aspect profiling scenarios with a score of 1o, network aspects with a total score of 11, and operating system aspects with a total score of 10. So it is obtained from the results of this study that all aspects of the application, network, and operating system were successful by 97% as measured based on the measurement metrics of each aspect.